1998
DOI: 10.1074/jbc.273.42.27625
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of UDP-GlcNAc:Galβ1–4GlcNAcβ1–3*Galβ1–4Glc(NAc)-R(GlcNAc to *Gal) β1,6N-Acetylglucosaminyltransferase from Hog Small Intestine

Abstract: A ␤1,6N-acetylglucosaminyltransferase (␤1-6GnT) responsible for the formation of the ␤1,6-branched poly-Nacetyllactosamine structure has been purified 210,000-fold in 2.4% yield from a homogenate of hog small intestine by successive column chromatographies involving CM-Sepharose FF, Ni 2؉ -chelating Sepharose FF, and UDP-hexanolamine-agarose, using an assay wherein pyridylaminated lacto-N-neotetraose (Gal␤1-4GlcNAc␤1-3Gal␤1-4Glc-PA) was used as an acceptor substrate, and the reaction product was Gal␤1-4Glc-NAc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…These results suggest that human and rabbit erythroid precursor cells contain IGnT that is the same as or similar to the IGnT cloned from PA-1 cells. Hog small intestine may have similar poly-N-acetyllactosamine structures as seen in erythrocytes and PA-1 cells, since a cIGnT was purified from this tissue (46). The present study also demonstrated that intrinsic properties of ␤4Gal-TI and iGnT are critical in forming short I-branches.…”
Section: Addition Of Multiple Short I-branches 9301supporting
confidence: 51%
“…These results suggest that human and rabbit erythroid precursor cells contain IGnT that is the same as or similar to the IGnT cloned from PA-1 cells. Hog small intestine may have similar poly-N-acetyllactosamine structures as seen in erythrocytes and PA-1 cells, since a cIGnT was purified from this tissue (46). The present study also demonstrated that intrinsic properties of ␤4Gal-TI and iGnT are critical in forming short I-branches.…”
Section: Addition Of Multiple Short I-branches 9301supporting
confidence: 51%
“…A human GlcNAc-transferase, termed cIGnT6 (centrally acting), which catalyses the transfer of GlcNAc to the 6-position of internal galactose residues of poly-N-lactosamine chains of N-linked glycans has been characterized (Mattila et al, 1998). A similar enzyme has been characterized from hog kidney (Sakamoto et al, 1998) and a related enzyme from rat serum has been used to synthesize a poly-branched decasaccharide with poly-N-acetyllactosamine units . dIGnT6 (distally acting) transfers GlcNAc to the 6-position of b-GlcNAc-(1 !…”
Section: Glcnac-transferasesmentioning
confidence: 99%
“…Hence, the elimination of the cytoplasmic and the membrane binding segment from the recombinant cIGnT6 of the present experiments was probably not associated with major changes in the substrate specificity. Consequently, it is worth noting that the recombinant cIGnT6 shares several features with the soluble cIGnT6 enzymes present in mammalian serum (18,31) and with the membrane-bound form of cIGnT6 recently isolated from hog small intestine by Sakamoto et al (46). The common features include (i) the ability to transfer one or several branches to midchain galactoses of long polylactosamine chains, (ii) the unability to react at peridistal galactose units in acceptors of the type GlcNAc␤1-3Gal␤1-4GlcNAc␤1-OR, and (iii) the inability to transfer at midchain galactoses that belong to Lewis x determinants.…”
Section: Discussionmentioning
confidence: 99%